Imaging of metastatic epidural spinal cord compression - Bai, James; Grant, Kinzya; Hussien, Amira; Kawakyu-O'Connor, Daniel (Frontiers in Radiology, 2022)
Metastatic epidural spinal cord compression presents in 5-10% of cancer patients and is becoming more common as advancement in cancer treatment prolongs survival in cancer patients (1-3). It represents an oncological emergency as metastatic epidural compression on adjacent neural structures, including the spinal cord, cauda equina, and exiting nerve roots may result in irreversible neurological deficits, pain, and spinal instability. Although management of metastatic epidural spinal cord compression remains palliative, early diagnosis and intervention may improve outcomes by preserving neurological function, stabilizing the vertebral column, and achieving localized tumor and pain control. Imaging serves an essential role in early diagnosis of metastatic epidural spinal cord compression, evaluation of the degree of spinal cord compression and extent of tumor burden, and pre-operative planning. This review focuses on imaging features and techniques for diagnosing metastatic epidural spinal cord compression, differential diagnosis, and management guidelines.